The Manning sisters - Macomber, Debbie. frey50; Macomber, Debbie; Macomber, Debbie (Don Mills, Ont. : MIRA Books, 2008)
When Seattle city gal Taylor Manning takes a teaching job in rural Montana, she finds the man of her dreams; and when her sister Christy comes to visit, she has to deal with the sizzle she feels when she meets the town sheriff.
The cowboy's lady -- The sheriff takes a wife.
Keywords: Man-woman relationships; Love stories